The Effectiveness of Using WhatsApp Social Media as Learning Media at Elementary School - Suroto, S.; Nandiyanto, Asep Bayu Dani (Indonesian Journal of Multidiciplinary Research, 2021)
The existence of the Corona Virus outbreak has changed the learning system in schools. Learning is carried out online, most elementary schools carry out online learning through WhatsApp social media. This is done so that the spread of the Corona Virus does not spread and does not cause casualties. This study aims to determine how effective online learning through WhatsApp social media is on students' knowledge at Elementary School. The results obtained are that learning activities carried out through WhatsApp tend to be less effective, this is because 35.1% of the 37 students still do not understand the material provided by the teacher and 43,% of students or nearly half of the 37 students who learn through WhatsApp feel burdened. Thus, the essence of the Education is not fulfilled.